Umbrella branding and external certification - Hendrik Hakenes; Martin Peitz (Max Planck Institute for Research on Collective Goods, 2008)
In a market environment with random detection of product quality, a firm can employ umbrella branding as a strategy to convince consumers of the high quality of its products. Alternatively, a firm can rely on external certification of the quality of one or both of its products. We characterize equilibria in which umbrella branding fully or partially substitutes for external certification. We also show that the potential to signal quality is improved if consumers condition their beliefs on the source of information, namely whether information comes from external certification or from random detection.
Keywords: L14; L15; M37; D82; 650; Umbrella branding; certification; signalling; Markenpolitik; Produktqualität; Warenkennzeichnung; Signalling; Asymmetrische Information; Theorie